Management of plant residue for cassava (Manihot esculenta) production on an acid ultisol in Southeastern Nigeria - Hulugalle, N.R.; Lal, R.; Opara-Nadi, O.A. (1987)
A study consisting of two experiments was conducted in southeastern Nigeria during 1983 and 1984 to determine whether cassava (Manihot esculenta Crantz) production on sandy, acid Ultisols could be improved by residue management techniques. One experiment studied the effect of location of Eupatorium odoratum mulch on soil properties and crop growth. A second experiment studied the effect of tillage system and Eupatorium odoratum mulch on soil properties and crop growth. In both experiments mulch was applied at an annual rate of 12 t∗ ha−1 (25% moisture content) in a split application at planting and 150 days after planting (DAP). No fertilizer was applied during the experiment. Concentration of mulch in the plant row resulted in values of within-row bulk density in the surface 0.10 m which were lower by 15% and 13% in 1983 and 1984, respectively. Tillage in combination with mulch reduced bulk density in the surface 0.10 m by an average of 10% and 9% in 1983 and 1984, respectively. No significant differences were found among other treatments. Soil chemical properties were unaffected by treatments in both experiments. Cassava tuber yield was unaffected by location of Eupatorium odoratum mulch. Both plowing and no-tillage when combined with mulch improved tuber yields. Cassava tuber yields of untilled plots were 16.8 and 12.7 t ha−1 during 1983–1984, and 13.1 and 8.3 t ha−1 during 1984–1985 in mulched and unmulched treatments, respectively. Tuber yields of tilled plots were 14.5 and 13.1 t ha−1 during 1983–1984, and 11.3 and 6.9 t ha−1 during 1984–1985 in mulched and unmulched treatments, respectively.